2010
DOI: 10.1128/jvi.00112-10
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interhost Evolutionary Dynamics of Equine Influenza Virus

Abstract: Determining the evolutionary basis of cross-species transmission and immune evasion is key to understanding the mechanisms that control the emergence of either new viruses or novel antigenic variants with pandemic potential. The hemagglutinin glycoprotein of influenza A viruses is a critical host range determinant and a major target of neutralizing antibodies. Equine influenza virus (EIV) is a significant pathogen of the horse that causes periodical outbreaks of disease even in populations with high vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
116
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(140 citation statements)
references
References 42 publications
18
116
6
Order By: Relevance
“…In IAVs, this research has focused on HA Murcia et al, 2010Murcia et al, , 2013. To the best of our knowledge, our study is the first to evaluate the intra-host diversity of the complete genome of IAV during infection of pigs using NGS, and our results are comparable with a recent study in children (Bourret et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In IAVs, this research has focused on HA Murcia et al, 2010Murcia et al, , 2013. To the best of our knowledge, our study is the first to evaluate the intra-host diversity of the complete genome of IAV during infection of pigs using NGS, and our results are comparable with a recent study in children (Bourret et al, 2015).…”
Section: Discussionsupporting
confidence: 80%
“…However, our results also showed that nucleotide substitutions can occur in the signal peptide and the HA2 region of the HA, which were not evaluated by Murcia et al (2012). In addition, other factors in our study, such as the group housing conditions, which facilitated greater interaction between pigs compared with previous studies where pairs of individuals were used to measure intra-host diversity of IAV (Hensley et al, 2009;Murcia et al, 2010Murcia et al, , 2012, may have had an effect on the increased overall genetic diversity.…”
Section: Discussioncontrasting
confidence: 50%
“…The transmission of multiple variants, observed in this study and in other transmission models (35)(36)(37)(38), suggests that the transmission bottleneck in IAV may not be so severe in many circumstances, which would enhance the diversity on which selection can act in transmission recipients. The mode of transmission likely impacts the size of the bottleneck.…”
Section: Discussionmentioning
confidence: 87%
“…In either case, the transmission of diversity may allow variants with moderate fitness advantages to emerge and grow out over the course of multiple transmission events. Preexisting immunity in guinea pigs has been shown to impact virus evolution during the course of a single infection (39), which raises the possibility of modeling in GPs viral evolution during transmission to animals with various states of preexisting immunity, as has been demonstrated in swine, horses, and dogs (36,37,40).…”
Section: Discussionmentioning
confidence: 99%
“…The key missing elements for understanding how treatment strength shapes the emergence and spread of resistance are (i) experimental data on both the shape of the conceptual curve (discussed above) and the location of the clinically neutral range of treatments on the drug pressure axis; (ii) a more thorough understanding of the cross-scale dynamics of anti-microbial resistance (see, e.g. [51]); and (iii) consideration of the different pathogen ecologies that determine how much competition between resistant and sensitive pathogens is likely to occur within a host. Quantitative predictions of resistance evolution, including the outcome of greatest public health interest, i.e.…”
Section: Future Directionsmentioning
confidence: 99%